Aspek Rancangan Miniature Automatic Drying Clothes Dengan Gsm Notifikasi - Rifki Saputra; Indra Yasri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Geographically, Indonesia is located on the equator which has two seasons, namely the rain season and the dry season. In the dry season, the sun's heat is needed for various needs, one of these is to drying wet clothes. The drying process cannot be monitored directly. Therefore, an automatic clothesline system was designed. This design uses Arduino Uno as a microcontroller. Light Dependent Resistor (LDR) sensor and rain sensor are used as inputs of this design. DC motor is applied to run the clothesline automatically. The notification in this design uses the GSM Module in the form of a short message and sent to the user.Keywords : Arduino Uno, LDR Sensor, Rain Sensor, GSM Module, Automatic clothesline